Development of Vision-Based Mobile Learning Media for Robotic System Competency Improvement in Vocational High School - Yana Yohana; Herlambang Sigit Pramono; Choirozyad Muhammad Hafidz (Journal of Vocational Education Studies, 2026)
This developmental research evaluates the development, performance, feasibility, and effectiveness of mobile robot learning media for goods transfer based on the HUSKYLENS vision sensor as an effort to improve robotic system competencies in vocational high schools. This research employs the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. The research site is located at SMK KB Pusdikpal Cimahi. The subjects of this research are 11th-grade students specializing in mechatronics engineering, and the object of this research is the learning media for a vision-based mobile robot used to move goods. In this study, the data analysis employed is quantitative descriptive analysis, which is used to describe the feasibility, functionality, and effectiveness of the study. Based on assessments from subject matter experts, media experts, and users, the findings of this study reveal that the mobile robot learning media for item transfer, utilizing the HUSKYLENS vision sensor, are considered valid and practical for use in the classroom. Hypothesis testing results indicate that the developed learning media are effective in enhancing students' competencies in robotic systems.